THE EVALUATION OF STOCHASTIC MODELING IN THE CONTEXT OF INSURANCE COMPANIES THROUGH THE ILLUSTRATION OF BRANCHING PROCESS - Rana, Md. Shohel; Rois, Rumana; Soheli, Sairatun Nesa (European Scientific Journal, ESJ, 2014)
Choice of stochastic modeling attempts to model the decision process of an individual or segment in a particular context. Choice models are able to predict with great accuracy how individuals would react in a particular situation. Discrete choice models determine the probability that a decision maker will take a certain action based upon several attributes and choices. This study provides evidence on the evaluation of an individual’s choice of alternative Insurance Companies. We have used some discrete choice stochastic models to assess the factors which influence on the evaluation of stochastic modeling in the context of Insurance Companies. Branching process model is used to construct a complete picture of Insurance companies’ activities in terms of their earning pattern and subscriber’s enrollment in their business. One of the most important factors in modeling of Insurance companies’ activities is to forecast the future profit and number of client’s involvement to know the long run performance of the company. This information can be extract by stochastic modeling. Especially for Branching process we consider Rupali Life Insurance Company. The branching process is introduced and evaluated to get idea of the distribution of client’s enrolment as well as it is also a stochastic population model based on explicit descriptions of individual life and reproduction .This model is also used in characterizing the distribution of the size of the population for different generations and the probability of extinction of the population.